1991
DOI: 10.3109/00365529108998608
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound, Computed Tomography, and Endoscopic Retrograde Cholangiopancreatography in the Detection of Obstructive Jaundice

Abstract: The purpose of this prospective study was to investigate the diagnostic accuracy of ultrasound (US), computed tomography (CT), and endoscopic retrograde cholangiopancreatography (ERCP) in the distinction between extrahepatic and intrahepatic causes of jaundice. The limit for the inclusion to the study was defined as a serum bilirubin concentration greater than or equal to 40 mumol/l. Altogether 187 jaundiced patients were studied. The sensitivities of US, CT, and ERCP were 63%, 77%, and 87%, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
57
1
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 28 publications
7
57
1
4
Order By: Relevance
“…Lindberg et al studied 64 cases of bile duct obstruction [17J and observed gall stone disease in 29 patients, pancreatitis in I patient, sclerosing cholangitis in 2 patients, pancreatic carcinoma in 18 patients, bile duct carcinoma in 9 patients, and gall bladder carcinoma in 5 patients. In another recent study [18] of 49 patients with extrahepatic jaundice, choledochal stone (72%) was the most common benign cause while pancreatic carcinoma (52%) was the most common malignant lesion. In our study, the Surgery of Obstructive Jaundice 77 cause of biliary obstruction was pancreatic cancer (34%), choledocholithiasis (27%), carcinoma of the gall bladder (II %) and cholangiocarcinoma (11%).…”
Section: Discussionmentioning
confidence: 91%
“…Lindberg et al studied 64 cases of bile duct obstruction [17J and observed gall stone disease in 29 patients, pancreatitis in I patient, sclerosing cholangitis in 2 patients, pancreatic carcinoma in 18 patients, bile duct carcinoma in 9 patients, and gall bladder carcinoma in 5 patients. In another recent study [18] of 49 patients with extrahepatic jaundice, choledochal stone (72%) was the most common benign cause while pancreatic carcinoma (52%) was the most common malignant lesion. In our study, the Surgery of Obstructive Jaundice 77 cause of biliary obstruction was pancreatic cancer (34%), choledocholithiasis (27%), carcinoma of the gall bladder (II %) and cholangiocarcinoma (11%).…”
Section: Discussionmentioning
confidence: 91%
“…In most cases of post-hepatic icterus ERCP is diagnostic particularly in combination with CT and US. 9 However, in cholangiocellular carcinoma some drawbacks of ERCP are known. 10,11 As ERCP was non-diagnostic an intrahepatic nature of the icterus was assumed necessitating a histologic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common causes depend on the population studied and include neoplasm (ranging from 18 to 86%) [1][2][3], calculous disease (varying from 5 to 48%) [1][2][3], and pancreatitis (in 2-27% of patients studied) [1][2][3]. Recently, we encountered a diagnostic challenge of a patient in whom silent obstructive jaundice developed, which proved to be of an etiology not previously reported.…”
mentioning
confidence: 95%
“…Ultrasonography has become the first imaging modality in obstructive jaundice; it has the ability to define the cause and level of obstruction [1][2][3]. The most common causes depend on the population studied and include neoplasm (ranging from 18 to 86%) [1][2][3], calculous disease (varying from 5 to 48%) [1][2][3], and pancreatitis (in 2-27% of patients studied) [1][2][3].…”
mentioning
confidence: 99%